Squalamine and Aminosterol Mimics Inhibit the Peptidoglycan Glycosyltransferase Activity of PBP1b - Adrien Boes; Jean Michel Brunel; Adeline Derouaux; Frédéric Kerff; Ahmed Bouhss; Thierry Touze; Eefjan Breukink; Mohammed Terrak (MDPI AG, 2020)
Peptidoglycan (PG) is an essential polymer of the bacterial cell wall and a major antibacterial target. Its synthesis requires glycosyltransferase (GTase) and transpeptidase enzymes that, respectively, catalyze glycan chain elongation and their cross-linking to form the protective sacculus of the bacterial cell. The GTase domain of bifunctional penicillin-binding proteins (PBPs) of class A, such as Escherichia coli PBP1b, belong to the GTase 51 family. These enzymes play an essential role in PG synthesis, and their specific inhibition by moenomycin was shown to lead to bacterial cell death. In this work, we report that the aminosterol squalamine and mimic compounds present an unexpected mode of action consisting in the inhibition of the GTase activity of the model enzyme PBP1b. In addition, selected compounds were able to specifically displace the lipid II from the active site in a fluorescence anisotropy assay, suggesting that they act as competitive inhibitors.